Psychoanalysis of Frida Kahlo’s work - Morales Miranda, Carmen (2014)
The psychoanalytic investigation of the work of an importantpersonality(Frida Kahlo in this essay) does not have the purposes that so often are attributed to an artist, that is to say “to dim radiance and to demolish constructions.” On the contrary, its only motivation is the extraordinary interest in all that can be discovered by such models. After reading her biography, such painful situations (poliomyelitis and accident) that Frida experienced are likely to be considered the reasonforthe content of her work. If this were the case, what turnedthose situations so traumatic?The analysis is based only on the author’s biographical description, the content of her writings (poems) and her paintings. Whenanalyzing Frida Kahlo’s work, we find 3 topics whichbesides-being recurrent in her work-need to be analyzed in order to understand the artist’s personality and creation. We imply masturbation, homosexuality and motherhood.